Assessment of cellulose in bark fibers of Thespesia populnea: Influence of stem maturity on fiber characterization. (15th May 2019) - Kathirselvam, M.; Kumaravel, A.; Arthanarieswaran, V.P.; Saravanakumar, S.S.
Graphical abstract: Highlights: Bark fibers of Thespesia populnea stem at different maturity was characterized. Fiber diameters increased from 150 μm to 200 μm with stem growth. Cellulose crystallinity ranges between 44% and 49% with ˜29.625 Å crystal size. Fibers tensile strength (557 ± 56.29 MPa for TPF20) declines by 39.4% on maturity. SEM and AFM micrographs illustrates that fiber surface becomes rough on maturity. Abstract: Cellulose is the key constituent of natural fibers and its proportion significantly varies with the growth of the plant. Hence, a study on the influence of plant maturity on fiber properties is essential to recognize optimal fiber source. In this investigation, cellulose fibers were successfully extracted from Thespesia populnea tree barks of approximately 10 mm–80 mm diameter stem and the influence of stem growth on physiochemical, thermal, mechanical and morphological characteristics of the fiber were investigated. The diameter of fiber increased from 150 μm to 200 μm with stem growth meanwhile its water uptake capability decreases by 13.8%. FTIR spectra and thermal analysis confirm the presence of cellulose compound in fiber structure, also the fiber can be stable up to 318 °C. The XRD outcome estimates 44–49% crystallinity index with an average crystallite size of 29.625 Å. Under the tensile load, fiber fails primarily by brittle fracture and its tensile strength ranges from 559 MPa to 329 MPa with an average elongation between 2.9% and 1.7%. Morphology analysis illustrates that fiber surface is becoming rough on maturity and can offer good interfacial strength when reinforced with composites.